Mixed Methods in Decision-Making Through Polar Coordinate Technique: Differences by Gender on Beach Handball Specialist - Vázquez-Diz, Juan A.; Morillo-Baro, Juan P.; Reigal, Rafael E.; Morales-Sánchez, Verónica; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
The aim of this research was to analyze decision making of the specialist in beach handball in the framework of mixed methods, and through the observation of their actions. To do this, and distinguishing it by genre, it was realized an analysis of polar coordinates using as behavior criteria the assist and completion of this specific position. A total of 24 sessions were observed with the computer software HOISAN, using a designed tool ad hoc. The model of observation used was nomothetic, punctual and multidimensional. The obtained results showed significant relations between the behavior criteria and conditional behaviors (mate), showing significant relations different for male and female categories. It was estimated statistically significant differences about the importance of the specialist in the development of the static attack in Beach handball and their influence in the final result of the match, based on their greater or lesser success in decision making. In male category it is highlighted that the specialist´s assists are not positively related to a favorable score and that the attack usually ends up in the central areas against closed defensive systems; in addition, their successful completion decisions are produced by means of launches in the central zone, also against closed defensive systems; however, in the female category, specialists ‘assists lead to end the attacks in flight on the far right against open defensive systems.